Nutrisi Efektif Mempercepat Penyembuhan Luka Perineum pada Ibu Post Partum (Systematic Review) - Wellina BR. Sebayang; Fitriana Ritonga (Politeknik Kesehatan Tanjung Karang, 2021)
Accelerated healing of perineal suture wounds during the puerperium is expected to prevent postpartum mothers from the danger of infection. Several methods can be done to accelerate the perineal wound healing process, one of which is by adding a high protein intake. This birth canal wound can become a container for bacteria to enter so that it can cause infection, trauma to the perineum can cause discomfort and pain during sexual intercourse, therefore handling this perineal wound is important. Good nutrition according to several studies can accelerate the wound healing process perineum. The purpose of this study was to determine effective nutrition in accelerating the healing of perineal wounds in postpartum mothers so that it can be used as an alternative method for patients who give birth. This study uses a systematic review method by examining journal articles published through the google scholar site of the reviewed journals. There are 6 methods of effective nutrition to accelerate perineal wound healing, are fish cork extract capsules, zinc supplements, eggs, red guava juice, catfish, pineapple juice, and honey.